PURPLE SWEET POTATO AND KIDNEY BEAN FLOUR PIE AS A HIGH FIBER SNACK FOR TYPE 2 DIABETES MELLITUS PATIENTS - Bahriyatul Ma'rifah; Ika Hikmah Maharani Sugiarto; Dewi Kusumawati (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Type 2 diabetes melitus (DM) is disorder of insulin secretion, decreased insulin action,or both, which cause elevated blood glucose level. Purple sweet potato flour and kidney bean flour contain high dietary fiber which can help control blood glucose level. This research aimed to determine the effect of different ratios of purple sweet potato flour and kidney bean flour on the pie’s organoleptik properties and nutrient content as a high fiber alternative snack for patients with type-2 DM. This experimental study employed a Completely Randomized Design (CRD) with 3 treatments of flour ratios F1 (60%: 40%), F2 (70%: 30%), and F3 (80%: 20%) with 2 repetitions. Data on nutrient content were analyzed using ANOVA and Duncan’s test, while organoleptic properties were analyzed using Kruskal-Wallis and Man-Whitney tests. The selection of the formulation used the Exponential Comparison Method (ECM). The results were significant effect on nutrient content pie and hedonic organoleptic properties of aroma parameters pie. The F3 selected formulation had nutrient content of water content 35.25%, ash 1.69%, protein 8.25%, fat 10.54%, carbohydrate 44.28%, and dietary fibre 15.15%. Pie serving (84g/3 pcs) contributed 10-15% of the RDA for with type 2 diabetes melitus patient. The pie can be claimed to be high in dietary fiber with a Nutrition Label Reference of 50.5%.